The Notary Liability as a General Officer in Making Banking Credit Agreements - Tri Wahyuni Bintang; Maryanto Maryanto (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2022)
The existence of a Notary must be impartial or neutral, so a Notary in making a deed may not involve himself in the deed, including the making of a deed for his family, also includes the prohibition of involving his family members as witnesses. If the Notary makes a technical error or is proven to have violated the Notary Position Act, from various sanctions depending on what mistakes were made by the Notary. If the Notary is asked by the client to provide the necessary information or advice related to the process of making the deed, if the information or advice given by the Notary is wrong or inappropriate and causes the client's loss, the Notary must be responsible as long as the information provided by the client is also true or not a lie. This study uses a sociological juridical approach.